2019
DOI: 10.1590/1807-1929/agriambi.v23n2p97-102
|View full text |Cite
|
Sign up to set email alerts
|

Production and quality of okra produced with mineral and organic fertilization

Abstract: Okra, Abelmoschus esculentus (L.) Moench, is a vegetable with annual fruit native to hot regions of Africa, well adapted to the conditions of the Northeast and Southeast regions of Brazil, where it is widely used by small farmers. This study aimed to evaluate the effect of mineral and organic fertilization on the production and quality of okra fruits. The experiment was conducted in randomized block design, with three replicates and eleven treatments defined according to a Baconian matrix. Treatments consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…It was also verified that fermentation with formulation 3 (100 g L -1 KCl) led to reductions in soluble solids, with a decrease of 20.38% when compared to formulation 4. The results obtained are higher than those found by Santos, Pereira, Medeiros, Costa and Pereira (2019), who evaluated the production and quality of okra fruits produced with mineral and organic fertilization and observed soluble solids contents ranging between 5.81 and 5.93 °Brix of fresh okra fruits. Therefore, it can be inferred that the adoption of lactic fermentation in okra fruits improved a sensory attribute (total soluble solids content) because, during the process of obtaining fermented pickles, lactic bacteria produce organic acids, aldehydes, ketones, and other organic compounds that confer special sensory characteristics to this product (Lima et al, 2006).…”
Section: Resultscontrasting
confidence: 76%
“…It was also verified that fermentation with formulation 3 (100 g L -1 KCl) led to reductions in soluble solids, with a decrease of 20.38% when compared to formulation 4. The results obtained are higher than those found by Santos, Pereira, Medeiros, Costa and Pereira (2019), who evaluated the production and quality of okra fruits produced with mineral and organic fertilization and observed soluble solids contents ranging between 5.81 and 5.93 °Brix of fresh okra fruits. Therefore, it can be inferred that the adoption of lactic fermentation in okra fruits improved a sensory attribute (total soluble solids content) because, during the process of obtaining fermented pickles, lactic bacteria produce organic acids, aldehydes, ketones, and other organic compounds that confer special sensory characteristics to this product (Lima et al, 2006).…”
Section: Resultscontrasting
confidence: 76%
“…Various treatments were also found to enhance ascorbic acid content. The enhancement of ascorbic acid content in okra crops treated with organic matter like neem cake and biofertilizer could be due to slowly but continuously providing both macro-and micronutrients that could have contributed to the assimilation of carbohydrates that help in the synthesis of ascorbic acid (Bahadur et al, 2009;Santos et al, 2019;El-Beltagi et al, 2019;. Moreover, Abd El-Aal and Salem (2018) showed that Azotobacter chroococcum EMCCN1458, Bacillus megaterium, Bacillus circulans and Azospirillum lipoferium D178 inoculation enhanced the total phenolics, flavonoids and ascorbic acid contents in the moringa plant.…”
Section: Discussionmentioning
confidence: 99%
“…Length of the fruits increased with increase in nutrient content of the briquettes. An increase in nitrogen content could enhance various biological processes in plants [40]. Weight of the fruits obtained by using organic briquette as a nutrient source was the highest for T10 (15.35±0.18 gm) and the lowest for control (12.07±0.15 gm), with T10 differing significantly (p<0.05) from all other treatments.…”
Section: Length and Weight Of The Fruitmentioning
confidence: 96%